Implementasi Metode Bermain Peran Dalam Meningkatkan Aspek Perkembangan Seni Anak Usia Dini - Ismi Rahmayanti, Ai; Kurnia, Aam; Nurdiansah, Nano (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The results of initial observations made with group B children at RA Nurul Amal showed that the children's artistic development was not optimal, this proved that the teacher only focused on coloring or drawing activities. Therefore, the children were less interested in other artistic activities. The aim of the study is to determine the development of children's art before and after the application of the roleplaying method. The type of research is Classroom Action Research (CAR) with the Kemis and Mc Taggat model approach which consisted of two cycles where each cycle has several stages such as: planning, implementation or action, observation or observation and reflection. Data collection techniques in this study use observation, documentation and performance. The results showed that the development of children's art before the implementation of the roleplaying method obtained an average value of 59. The process of implementing the roleplaying method in each cycle; Teacher activity in cycle I was 69% and in cycle II was 96%. Children's activity in cycle I was 83% good and in cycle II was 98%. The development of children's art after the implementation of the play method, the first cycle has an average value of 69, the second cycle is 85 with. It can be concluded that the roleplaying method is proven to improve children's artistic development at RA Nurul Amal. Thus, the hypothesis proposed of this study is accepted